Shear Wall Provision Influence on Medium Rise Multi-Storey Framed Building in Maiduguri - Alkali, A. M.; Onundi, L. O.; Mohammed, K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This study compares the aerodynamic behaviour of medium rise multi-storey frame structures with and without shear walls using the local wind gust of Maiduguri (47m/s) as primary data. The wind assessment was carried out in accordance with recommendations of British Standard and other relevant specifications. Analysis of the structural system was carried out using Extended Three-dimensional Analysis of Building System (ETABS) software; where the forces, maximum floor drifts and stresses are obtained and compared. The result shows that, the displacement fora 15 storey building with shear wall was 91.44% less than same without shear walls while with increasing storey height, the differences reduce; for example, the displacement for 20 storey building with shear wall showed 81.5% lesser than same building without shear wall. This signifies that building with shear wall resist aerodynamic load more efficiently principally due to the influences of the rigidity and strategic locations of the shear wall in the building. The shear walls are usually effective in stabilizing displacements on medium rise multi-storey buildings subjected to lateral forces from wind, seismic and explosive to satisfy serviceability criteria of H/500 stipulated by most conventional standard.